Indirect field-oriented control of induction motors is robustly globally stable - De Wit, Paul A.S.; Ortega, Romeo; Mareels, Iven (Automatica (Oxford), 1996)
Field orientation, in one of its many forms, is an established control method for high dynamic performance AC drives. In particular, for induction motors, indirect fieldoriented control is a simple and highly reliable scheme which has become the de facto industry standard. In spite of its widespread popularity no rigorous stability proof for this controller was available in the literature. In a recent paper (Ortega et al, 1995) [Ortega, R., D. Taoutaou, R. Rabinovici and J. P. Vilain (1995). On field oriented and passivity-based control of induction motors: downward compatibility. In Proc. IFAC NOLCOS Conf., Tahoe City, CA.] we have shown that, in speed regulation tasks with constant load torque and current-fed machines, indirect field-oriented control is globally asymptotically stable provided the motor rotor resistance is exactly known. It is well known that this parameter is subject to significant changes during the machine operation, hence the question of the robustness of this stability result remained to be established. In this paper we provide some answers to this question. First, we use basic input-output theory to derive sufficient conditions on the motor and controller parameters for global boundedness of all solutions. Then, we give necessary and sufficient conditions for the uniqueness of the equilibrium point of the (nonlinear) closed loop, which interestingly enough allows for a 200% error in the rotor resistance estimate. Finally, we give conditions on the motor and controller parameters, and the speed and rotor flux norm reference values that insure (global or local) asymptotic stability or instability of the equilibrium. This analysis is based on a nonlinear change of coordinates and classical Lyapunov stability theory.